Adoptive Immunotherapy with Cl-IB-MECA-Treated CD8+ T Cells Reduces Melanoma Growth in Mice - Montinaro, Antonella; Forte, Giovanni; Sorrentino, Rosalinda; Luciano, Antonio; Palma, Giuseppe; Arra, Claudio; Adcock, Ian M.; Pinto, Aldo; Morello, Silvana (PLOS ONE, 2012)
Cl-IB-MECA is a selective A3 adenosine receptor agonist, which plays a crucial role in limiting tumor progression. In mice, Cl-IB-MECA administration enhances the anti-tumor T cell-mediated response. However, little is known about the activity of Cl-IB-MECA on CD8+ T cells. The aim of this study was to investigate the effect of ex vivo Cl-IB-MECA treatment of CD8+ T cells, adoptively transferred in melanoma-bearing mice. Adoptive transfer of Cl-IB-MECA-treated CD8+ T cells or a single administration of Cl-IB-MECA (20 ng/mouse) inhibited tumor growth compared with the control group and significantly improved mouse survival. This was associated with the release of Th1-type cytokines and a greater influx of mature Langerin+ dendritic cells (LCs) into the tumor microenvironment. CD8+ T cells treated with Cl-IB-MECA released TNF-α which plays a critical role in the therapeutic efficacy of these cells when injected to mice. Indeed, neutralization of TNF-α by a specific monoclonal Ab significantly blocked the anti-tumor activity of Cl-IB-MECA-treated T cells. This was due to the reduction in levels of cytotoxic cytokines and the presence of fewer LCs. In conclusion, these studies reveal that ex vivo treatment with Cl-IB-MECA improves CD8+ T cell adoptive immunotherapy for melanoma in a TNF-α-dependent manner.